The Effect of COVID-19 on Police Activities: Traffic Stops, Arrests, and Use of Force - Demir, Mustafa (Criminal justice review, 2024)
COVID-19 may affect police activities (i.e., traffic stops, arrests, and use of force) due to public compliance with COVID-19 restrictions, changes in individuals’ daily activities, and health threats posed by COVID-19. The purpose of this research is to examine the effects of COVID-19 on police activities and the trends in these activities in Burlington, Vermont. The data that measured arrests, traffic stops, and use of force were obtained from the Burlington Police Department website and covered the period from December 10, 2018 through June 14, 2021. Then, the daily time-series data for arrest rate, use of force rate, and traffic stop rate were created (N = 918; 459 days pre-COVID-19 and 459 days during COVID-19). The results showed that COVID-19 statistically significantly decreased traffic stops and arrests, but not use of force on the day immediately following the implementation of the COVID-19 restrictions and then remained stable over time. However, no significant change was detected in the trends of arrests, traffic stops, and use of force before and during the COVID-19 period. COVID-19 had a significant immediate and lasting effect on traffic stops and arrests, but not use of force.